Effects of different recovery interventions on anaerobic performances following preseason soccer training - Tessitore, A.; Meeusen, R.; Cortis, C.; Capranica, L. (The Journal of Strength and Conditioning Research, 2007)
In the preseason soccer training, morning and afternoon training sessions often are scheduled daily. The high frequency of training sessions could place heavy strain on biological systems, and it is necessary to apply proper recovery strategies for improving the players' capability to regain an adequate working state for subsequent training units. However, the effect of recovery interventions following soccer training units is debatable, due to a lack of studies performed in field situations. The aim of this study was to examine, during a 21-day preseason soccer training, the most effective recovery intervention (i.e., passive, dry-aerobic exercises, water-aerobic exercises, electrostimulation) on anaerobic performances (i.e., squat jump, countermovement jump, bounce jumping, and 10-m sprint) and subjective ratings (i.e., perceived exertion and muscle pain), with the conditions before the intervention controlled and standardized. Twelve young (age: 18.1 +/- 1.2 years) elite soccer players participated. Data were collected on 4 occasions 2 days apart and at the same time of the day. Activity and dietary intake were replicated on each occasion. After baseline measurements, participants performed a standardized training during which their heart rates and ratings of perceived exertion were recorded. This was followed by a 20-minute recovery intervention. After a 5-hour rest, athletes' ratings of muscle pain were recorded prior to a second test session. There were no significant differences in exercise intensities and baseline anaerobic performances. Significantly (p > 0.01) better performances were observed in the afternoon. Although no main effect of recovery intervention was observed on anaerobic performances, dry-aerobic exercises (0.6 +/- 0.9) and electrostimulation (0.6 +/- 1.2) were more beneficial (p > 0.01) than water-aerobic exercises (2.1 +/- 1.1) and passive rest (2.1 +/- 1.7) for reducing muscle pain, which could affect the player's working ability.